Direct Zakat in the Context of Hablun Minallah Wa Hablum Minannas - Miftahurrahmah Miftahurrahmah; Riska Fauziah Hayati; Abdul Karim Hidayatullah; Muhammad Rais (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
Paying zakat to those who can afford it is a religious way to prevent wealth from accumulating only for certain people. Many zakat institutions have problems in collecting and distributing it. In response, some muzakki (zakat payers) have chosen to directly distribute zakat to mustahiq (eligible recipients). This study aims to explore the phenomenon of direct zakat distribution within the context of Hablum Minallah (relationship with Allah) and Hablum Minannas (relationship with fellow humans) and to examine its implications for zakat institutions. The research method used in this study is a literature review, gathering relevant references on the topic. The study focuses on direct zakat distributed to the community and on zakat institutions operating in Padang Pariaman Regency, West Sumatra. The findings of this study suggest that direct zakat distribution within the context of Hablum Minallah and Hablum Minannas not only serves as an expression of devotion to Allah but also fosters greater connection and care between muzakki and the surrounding community receiving zakat. Additionally, the study examines the implications of direct zakat on zakat institutions, recommending that these institutions develop more concrete programs and engage in stronger collaboration with all relevant stakeholders.